At The Top of the Interneuronal Pyramid - Calretinin Expressing Cortical Interneurons - Filip Barinka; Zsofia Magloczky; Nada Zecevic (Frontiers Media SA, 2021)
It is in general well appreciated that the cortical interneurons play various important roles in cortical neuronal networks both in normal and pathological states. Based on connectivity pattern, developmental, morphological and electrophysiological properties, distinct subgroups of GABAergic interneurons can be differentiated in the neocortex as well as in the hippocampal formation. In this E-Book, we are focusing our attention on inhibitory interneurons expressing calcium-binding protein calretinin (CR). The aim of the E-Book is to consolidate the knowledge about this interneuronal population and to inspire further research on the function and malfunction of these neurons, which – functionally – seem to stand "at the top of the pyramid" of cortical interneuronal types.